The Implementation of Talent Management System in Retaining Millennial Generation Employees - Fatmasari Endayani; Ernita Dian Puspasari; Saman Saman (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the implementation of the talent management system in the context of retaining millennial generation employees. Using a qualitative research method with a literature study approach, this study explores the characteristics and expectations of millennial employees, the factors that affect the effectiveness of talent management, and the challenges in its implementation. The results of the study show that the success of talent management for the millennial generation is greatly influenced by the integration of digital technology, personalization of development programs, and work flexibility. Organizational and leadership support, along with a culture that supports innovation and collaboration, are critical factors in increasing engagement and talent retention. The research also identified key challenges such as the generation gap and the complexity of measuring program effectiveness. An effective talent management model requires a holistic approach that aligns the various components of the system, supported by comprehensive metrics for program impact evaluation. These findings make a significant contribution to the development of talent management practices that are adaptive to the needs of the millennial generation